Increasing the Visibility of Scientific Data in Armenia Using Persistent Identifiers - Grigoryan, Hayk A. (Mathematical Problems of Computer Science, 2021)
During the development of computer technologies, the scientific research becomes more data intensive and collective than in the past. Data practices of researchers such as data sharing, discovery, reuse and preservation can be useful for other researchers in the same domain. Data sharing allows the verification of results and extends scientific research from previous results. Many scientific fields such as Biology, Astronomy, Weather forecast, etc., produce a vast amount of data, these data need to be shared and increase its accessibility, because sharing data has an important role for today’s science communities. In this paper, we introduce a deployed infrastructure to enable data-sharing using metadata which increases the accessibility of this data.